PENGARUH SOSIAL EKONOMI, GAYA HIDUP, PSIKOLOGIS KONSUMEN, DAN KELOMPOK REFERENSI TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE BLACKBERRY (Studi Pada Pelajar SMA Kesatrian 1 Semarang) - Ika Windu Winata, 11.05.51.0038 (Students Journal of Economic and Management, 2015)
This research is to analyze and test of the influence of socio-economic, lifestyle, consumer psychology, reference groups for blackberry mobile phone purchasing decisions. Object of study in this paper is SMA Kesatrian 1 Semarang. The sampling technique in this research is the use of sample random sampling (random) of the 100 respondents in the sample data collection method using a questionnaire (questionnaire) by distributing a list of questions to the respondent in order to obtain information. The data were analyzed using factor analysis to test the validity of the question items, Cronbach alpha formula to test the reliability of each of the independent variables were tested by regression analysis. The results of the research are: (1) Social economy has a positive and significant impact on purchasing decisions. (2) Lifestyle has a positive and significant impact on purchasing decisions. (3) Psychological consumer has a positive and significant impact on purchasing decisions. (4) The reference group has a positive and significant impact on purchasing decisions. Keywords : Social Economy, Lifestyle, Consumer Psychological and Reference Group.